The Financial Decentralization Policy for Local Development in Cameroon: An Econometric Analysis - TCHOUASSI, Gerard; DZOU, Pierre Patrick (Journal of Empirical Studies, 2020)
The objective of this article is to show the effectiveness of financial decentralization policy in the process of local development. In order to do so, we analyze the financial decentralization as a determinant of the effectiveness of local development in Cameroon. To achieve the main objective, we have used the data grouped together after the exploitation of the communal development plans. Using the Data Environment Analysis (DEA) model, we have obtained interesting results: When the budget allocated to decentralized territorial collectivities (DTC) is increased by 1%, this makes possible an increase of 13 points of the achievement of non-revenue generating projects and by11 points, those of income-generating projects at the level of DTC. When the budget increases by 10 points, there is an increase of 130 points of the achievements of non-revenue generating projects and 110 points of those of income-generating projects. The increase of financial resources at the level of DTCs would create a reasonable increase of investments in socio collective projects and in basic infrastructures. This leads to a drastic reduction in the unemployment rate. We can recommend to the Government to implement strategies that can reinforce the practice of financial decentralization and ensure decentralized governance. The financial decentralization is an economic indicator that can bring growth and development.